Model Spasial Deforestasi dalam Rantai Pasok Komoditas Kelapa Sawit di Kawasan Ekosistem Leuser (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2026)
The Leuser Ecosystem Area (Kawasan Ekosistem Leuser, KEL), covering more than 2.6 million hectares in Aceh and North Sumatra, Indonesia, is a globally important biodiversity landscape and carbon reserve. It provides habitat for critically endangered Sumatran elephants, orangutans, rhinoceroses, and tigers, while also supporting essential ecosystem services for surrounding communities. However, continued land-use change, particularly oil palm expansion, has increased pressure on forest cover and landscape integrity. This study integrates remote sensing, Cellular Automata-based spatial modeling, and palm oil supply chain analysis to assess historical land-cover change, future oil palm expansion, and deforestation risk in the KEL. Land-cover classification was conducted for 2016, 2020, and 2024 using multi-source satellite imagery, followed by spatial modeling to project land-cover change until 2032. The results show that oil palm plantations increased from 34,956.25 ha in 2016 to 117,112.50 ha in 2024, with projections indicating further expansion to 176,387.50 ha by 2032. The observed expansion between 2016 and 2024 was partly associated with the conversion of forest areas and shrub/agricultural lands. The model incorporated spatial drivers such as proximity to palm oil mills, road networks, settlements, existing oil palm areas, and mill processing capacity. The projected expansion indicates that future deforestation risk is likely to concentrate in areas with strong accessibility and supply chain connectivity. The novelty of this study lies in linking spatial deforestation modeling with palm oil supply chain analysis, allowing deforestation risk to be assessed not only as land-cover change, but also in relation to plantation, mill, and refinery nodes relevant to deforestation-free supply chain commitments. The findings provide a spatially explicit framework to support conservation planning, supply chain traceability, and risk-based mitigation in the Leuser Ecosystem.